THE ANALYSIS OF CHARACTER EDUCATION IN THE IMPLEMENTATION OF LEARNING USING THE INDEPENDENT CURRICULUM AT SDN 2 SENGON - Yudha Julistiyana, Maria Ulfa (JOSAR (Journal of Students Academic Research), 2024)
Researchers intend to research the role of character education in the implementation of independent curriculum learning in class 4 of SDN 2 Sengon. This research can later become a benchmark for teachers in providing character education-based learning in the learning process using the independent curriculum, so that teachers can further develop the character education process that is applied to learning using the independent curriculum. In the research that was carried out, researchers found the results of the character education system and process in the learning process using the independent curriculum in class 4 of SDN 2 Sengon. This research uses a descriptive qualitative method, while the approach used is descriptive. The role of the researcher in this research is as a full observer. There are 2 types of research data sources in this study, namely primary data sources, namely class teachers, school principals and class IV students at SDN 2 Sengon. Meanwhile, secondary data sources are taken from data and documentation of research results. The data collection method used by researchers is observation, interviews and questionnaires. From interviews conducted by researchers with the Principal of SDN 2 Sengon, researchers found that SDN 2 Sengon globally emphasizes character education, especially religious character. This is shown in the activities that are always carried out every day at school. These activities include TPA Fiqh, Al-Qur'an, Hadith activities as well as congregational Dhuha and midday prayers. However, on the other hand, SDN 2 Sengon also emphasizes other characters, for example nationalism and independence. These character development activities are always developed through daily activities for students and are cultivated so that these characters can be attached to students. Through the results described above, it can be concluded that character education activities have been implemented well at SDN 2 Sengon. This is reinforced by the results of observations of character development which is considered to continue to increase every month.